The Effect of The Lester Model on Achieving And Increasing Engagement In Learning Among Students of The Institute of Fine Arts (Journal of the College of Basic Education, 2025)
The current research aims to identify the effect of the Leicester model on achieving and increasing engagement in learning among students of the Institute of Fine Arts in the subject of Art History. The researcher adopted the experimental design with two groups with an achievement (cognitive) test. The research sample consisted of (20) students distributed They were distributed equally into the two experimental and control groups. The researcher prepared two tools for his research, which were the achievement test and the engagement scale. To reach the research results, the researcher used a set of statistical methods, including: Mann-Whitney test for two independent samples, Kuder-Richardson equation 20 for the reliability of the achievement test, Pearson correlation, and Farco-Nbach for the reliability of the engagement scale, the difficulty factor for the objective items, the effectiveness of false alternatives, and measuring the effect size.